2022
DOI: 10.1186/s12889-022-14746-w
|View full text |Cite
|
Sign up to set email alerts
|

Resilience mediates parenting style associated school bullying victimization in Chinese children and adolescents

Abstract: Background Existing evidence has shown that negative parenting style elevates the risk of school bullying victimization in children and adolescents. Resilience may play as a mediating factor in this association. However, this hypothesis has not been investigated. Methods In this cross-sectional study, a total of 4582 Chinese children and adolescents had been surveyed by self-administered questionnaire. The Chinese version of Egna Minnen av. Barndom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The second objective was to examine whether maternal and paternal (i.e., risk and protective) factors are differently associated with bullying victimization (i.e., traditional and cyber). Overall, our results indicated that the practices of both parents impact a child's risk of being bullied and are supported by previous studies that have reported similarities in how mothers' and fathers' relationships with their children influence traditional (e.g., Chen et al, 2022;Freitas et al, 2022) or cyberbullying victimization (e.g., Larrañaga et al, 2016;Garaigordobil & Navarro, 2022). Furthermore, our results indicated that maternal and paternal factors were common predictors of traditional and cyberbullying victimization, showing associations of similar magnitude.…”
Section: The Impact Of Maternal and Paternal Factors On Bullying Vict...supporting
confidence: 87%
See 3 more Smart Citations
“…The second objective was to examine whether maternal and paternal (i.e., risk and protective) factors are differently associated with bullying victimization (i.e., traditional and cyber). Overall, our results indicated that the practices of both parents impact a child's risk of being bullied and are supported by previous studies that have reported similarities in how mothers' and fathers' relationships with their children influence traditional (e.g., Chen et al, 2022;Freitas et al, 2022) or cyberbullying victimization (e.g., Larrañaga et al, 2016;Garaigordobil & Navarro, 2022). Furthermore, our results indicated that maternal and paternal factors were common predictors of traditional and cyberbullying victimization, showing associations of similar magnitude.…”
Section: The Impact Of Maternal and Paternal Factors On Bullying Vict...supporting
confidence: 87%
“…Taken together, our results suggest that parents may have a greater impact on bullying victimization occurring in the offline context. All parental factors directed at the child (i.e., parental rejection, control, parenting styles, and monitoring) and the relationship between parents (i.e., inter-parental Table 2 Effect sizes of the associations between parental protective and risk factors and traditional bullying victimization k number of studies, N number of participants, LCI lower confidence interval, UCI upper confidence interval, I 2 percentage of heterogeneity, NA not applicable a All results are reported with r correlation (significant results are marked with italic) b Outliers were defined as studies in which the 95% CI was outside the 95% CI of the pooled studies: Alcantara et al ( 2017 c Fair and good studies were defined as studies which had less than 50% (respectively 75% for good quality) risk of bias accordingly to NIH Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies NIH (2014) detailed in Table A.1 d Beran and Violato (2004), Chen et al (2022), Chui et al (2022, Garaigordobil and Machimbarrena (2017), Hokada et al (2006), Hong et al (2021a), Ioannidou et al (2021, Kokkinos and Panayiotou (2007), Krisnana et al (2021), Lardier et al (2016 conflict) were relevant in protecting or putting children at risk of being bullied at school. Of these, the dimensions of parental rejection have been previously examined through a meta-analysis, showing that parental warmth, in the form of communication and trust, reduced the risk of being bullied, while parental rejection, in the form of alienation, increased the risk (Ward et al, 2018).…”
Section: The Effects Of Parental Factors On Traditional and Cyberbull...mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this study found that psychological resilience signi cantly negatively predicts the occurrence of school bullying, meaning that lower levels of psychological resilience increase the risk of experiencing bullying, whereas higher levels decrease it. Scholars [73][74][75][76] argue that psychological resilience is a protective factor against school bullying, with a negative correlation between personal resilience and bullying incidents; higher personal resilience leads to reduced bullying risks. Research also con rms [29,40,44,69,77] that enhancing individual psychological resilience can buffer the impact of negative life events, aiding victims in overcoming crises, reducing the harm caused by bullying incidents, and lowering the risk of being bullied again.…”
Section: Intermediary Role Of Psychological Resiliencementioning
confidence: 99%